Northward Pathway Across the Tropical North Pacific Ocean Revealed by Surface Salinity: How do El Niño Anomalies Reach Hawaii?. Issue 4 (20th April 2018) - Hasson, Audrey; Puy, Martin; Boutin, Jacqueline; Guilyardi, Eric; Morrow, Rosemary
Abstract: Using the unprecedented 7 year monitoring of sea surface salinity (SSS) from the Soil Moisture Ocean Salinity (SMOS) satellite mission, an unexpected large‐scale anomaly at 20°N is studied in the tropical Pacific Ocean following the 2015‐2016 extreme El Niño event. This basin‐wide negative anomaly (below −0.3) is present in October 2015 between 15 and 25°N, reaching the Hawaiian archipelago. It has not been previously observed during El Niño events. It is accompanied by a negative equatorial SSS anomaly at the dateline (below −0.5) which has been previously described as an El Niño‐associated SSS anomaly. A wide range of observations (in situ and space‐borne) and a state‐of‐the‐art ocean model simulation are used together to characterize and understand the mechanisms leading to this singular SSS signal. The extra‐equatorial negative SSS anomaly is found to be a superposition of a persisting SSS anomaly due to the 2014 weak El Niño and of the larger 2015‐2016 El Niño SSS anomaly. Both were advected northward in the tropical current system by the mean Ekman currents and hypothetically by instabilities in the zonal currents patterns. An analysis of analogous structures in the past 20 years shows that this northward displacement of SSS anomalies is not El Niño specific, even if their advection is enhanced during El Niño events. This study shows that when surface freshwater fluxes are weak SSS, unlike sea surface temperature, can be used to trace water mass displacement for up to 20 months. Key Points: 20°N large‐scale extra‐equatorial sea surface salinity anomalies associated with historical 2015 El Niño A combination of In situ, modeled and SMOS surface salinity products give an unprecedented insight on the anomalies and mechanisms 20°N SSS anomaly is a superposition of a persisting weak El Niño 2014 anomaly and 2015 El Niño anomaly both advected by mean Ekman currents